The Effectiveness of Collaborative Learning with Group Investigation in Mathematics Lessons in Elementary School Education in South Tangerang, Indonesia - Okta Rosfiani; Windu Syaeful Ridwan; Ardiyanti, Heni; Cika Auliya Nurrohmah; Fitrha Ramadhan; Afandy Muharrom (Enigma in Education, 2024)
This research examines the effectiveness of collaborative learning with group investigations in mathematics lessons in South Tangerang elementary schools. A quasi-experimental design with two groups (experimental and control) was used. The sample consisted of 60 fifth grade elementary school students who were chosen randomly. The experimental group (n=30) took part in collaborative learning with group investigation, while the control group (n=30) took part in traditional learning. The results show that there is a significant difference in mathematics learning outcomes between the two groups (t = 2.45; p = 0.017). The experimental group showed higher learning outcomes (M = 82.50; SD = 7.12) compared to the control group (M = 75.83; SD = 6.47). This research shows that collaborative learning with group investigations is effective in improving elementary school students' mathematics learning outcomes. This research concludes that collaborative learning with group investigation is an effective learning strategy for improving elementary school students' mathematics learning outcomes.